Coupling coordination analysis of resources, economy, and ecology in the Yellow River Basin - Guanhang Sui; Huixiao Wang; Siyang Cai; Wendi Cui (Ecological Indicators, 2023)
The development of the Yellow River Basin (YRB) has been constrained by resource utilization, ecological conservation, and economic growth. The aim of this study was to establish a theoretical framework for characterizing the relationships among resources, economy, and ecology in the YRB using panel data and remote sensing data from nine provinces in the basin from 2002 to 2022. Furthermore, a coupling coordination degree model and geographical detector model were used to evaluate the spatiotemporal coupling and relevant factors. Our findings were manifold. (1) The coupling coordination degree in the YRB and its provinces has improved to varying degrees, with upstream provinces showing stronger coordination than midstream and downstream provinces. (2) The most significant growth rates were observed during 2002–2006 and 2014–2018. However, a noticeable decline in the coupling coordination degree occurred during 2006–2010, indicating that ecological constraints and negative effects were pronounced when resource constraints were not apparent. (3) The average coupling coordination degree of resources, economy, and ecology in the YRB in 2022 was 0.684. Excellent coordination was observed in Shandong Province and Henan Province, and good coordination was observed in Shaanxi Province and Shanxi Province. (4) In the initial part of the study period, the water resource supply, demand, and allocation had strong effects on the coordination degree. Over time, the focus shifted from a single system to multiple systems, which increased the similarity in the explanatory power of different factors. Additionally, an in-depth analysis using the coupling coordination degree and relevant factors was conducted to characterize the policy orientations of different periods in the YRB. Policy recommendations were provided on the basis of the natural conditions and socio-economic conditions of the YRB. The findings of this study have implications for coupling coordination relationships and high-quality development in the YRB. Generally, our results provide key insights that will aid coordinated and sustainable regional development.